2014
DOI: 10.1620/tjem.232.207
|View full text |Cite
|
Sign up to set email alerts
|

A Single Trial of Transcutaneous Electrical Nerve Stimulation Reduces Chronic Neuropathic Pain Following Median Nerve Injury in Rats

Abstract: Neuropathic pain is a devastating chronic condition and is often induced in the upper limb following nerve injury or damage. Various drugs or surgical methods have been used to manage neuropathic pain; however, these are frequently accompanied by undesirable side effects. Transcutaneous electrical nerve stimulation (TENS) is a safe and non-invasive intervention that has been used to alleviate different types of pain in the clinic, but it is unclear whether TENS can improve chronic neuropathic pain in the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Percutaneous electrical stimulation was shown to alleviate pain in cases of musculoskeletal pain, arthritis pain, low back pain, neuropathic pain, and post-operative pain [ 22 , 23 , 29 , 30 ]. Low-frequency electrical stimulation induced analgesia by inhibiting pain transmission through the recruitment of the descending inhibitory system; however, high-frequency (80–100 Hz) stimulation activated the gate control by stimulation A-beta fibers [ 31 ].There were various inconsistencies amongst previous studies with respect to the therapeutic effect according to the frequencies tested [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous electrical stimulation was shown to alleviate pain in cases of musculoskeletal pain, arthritis pain, low back pain, neuropathic pain, and post-operative pain [ 22 , 23 , 29 , 30 ]. Low-frequency electrical stimulation induced analgesia by inhibiting pain transmission through the recruitment of the descending inhibitory system; however, high-frequency (80–100 Hz) stimulation activated the gate control by stimulation A-beta fibers [ 31 ].There were various inconsistencies amongst previous studies with respect to the therapeutic effect according to the frequencies tested [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dorsal root ganglia cells were dissected from embryonic Sprague–Dawley rat at the embryonic days 14–15 according to previous report [ 20 , 22 , 23 ]. The DRGs were incubated with 0.25% trypsin at 37 °C for 15 min and were dissociated, washed and re-suspended with Neurobasal medium containing 2% B27 (sigma, Inc.), 0.3% l -glutamine and 100 ng/ml nerve growth factor.…”
Section: Methodsmentioning
confidence: 99%
“…Cho et al studied the analgesic effects of conventional TENS in a rat chronic neuropathic pain model created by ligation of the median nerve. 104 Conventional TENS was applied for 20 minutes ipsilaterally or contralaterally to the nerve injury. Ipsilateral TENS application reduced mechanical, cold, and thermal allodynia compared to sham-treated rats.…”
Section: Animal Models Of Painmentioning
confidence: 99%
“…Many studies have shown that TENS is effective for a wide variety of pain, e.g. cancer pain 5 ) , neuropathic pain 6 ) , and low back pain 7 ) .…”
Section: Introductionmentioning
confidence: 99%